The Tomb of D. Rodrigo Sanches: the rediscovery of an iconographic program - Carla Varela Fernandes (Medievalista, 2014)
The Tomb (Cenotaph) of D. Rodrigo Sanches (illegitimate son of King Sancho I) was recently removed from the arcosolium that housed it in the cloister of the Monastery of S. Salvador Grijó since 1626.This transfer, which had as its main consequence the possibility of visualization of the remaining sides of the chest tomb, as well as the improved visualization of the tomb effigy and other figures of the slab brought interesting news to the panorama of History of Portuguese Medieval Art, from the iconographic point of view and also from the plastic/aesthetic point of view, since all faces are carved. Therefore, this is the moment to rewrite the analysis of this work of late-Romanesque sculpture, to place it regarding all the represented, to attempt to decode the main intentions of his commissioner and seek its integration into a broader geographic universe, from the artistic point of view, (peninsular and trans-Pyrenean). The responsibility of being the first time that the work is studied in its entirety leads to the presentation of proposals, interpretive hypotheses, rather than conclusions.